What Matters in the Mirror of Time: Why Lucretius' Symmetry Argument Fails. Issue 4 (2nd October 2019) - Meier, Lukas J.
Abstract: By appealing to the similarity between pre-vital and post-mortem nonexistence, Lucretius famously tried to show that our anxiety about death was irrational. His so-called Symmetry Argument has been attacked in various ways, but all of these strategies are themselves problematic. In this paper, I propose a new approach to undermining the argument: when Parfit's distinction between identity and what matters is applied, not diachronically (as he uses it) but across possible worlds, the alleged symmetry can be broken. Although the pre-vital and posthumous time spans that we could have experienced are indeed analogous with respect to our identity, they are not analogous with respect to psychological continuity, which forms the basis of prudential concern. Lucretius even anticipated the Parfitian distinction. He did not, however, notice the significance that it has for his Symmetry Argument.